(untitled) (Advances in Applied Mathematics and Mechanics, 2025)
The discretization of the fractional regime-switching option pricing model leads to the linear system with the block diagonal and Kronecker product structure. A fast matrix splitting iteration method is presented to solve the discrete system. Theoretical analyses prove the convergence of the proposed iteration method. Numerical experiments show that the new method is efficient and outperforms the existing methods in terms of the number of iteration steps and the elapsed CPU time.